Revitalisasi Identitas Kebangsaan Anak Imigran Indonesia Melalui Budaya Nusantara di Malaysia - Sekar Ayu; Nazwa Azzahra; Hafiza Zahra Aljawawi; Saffina Sajidah; Wina Aditya Zahra; Lyona Beby Melinda; Miza Nina Adlini (Jurnal Abdimas Indonesia, 2025)
The International Community Service Program (KKN) UIN Sumatera Utara in Selangor, Malaysia, is a form of cross-border community service focused on educating and strengthening the national identity of Indonesian immigrant children. Their situation demonstrates limited access to formal education, a shortage of teachers, and low basic literacy skills, with some children older than their grade level yet still unable to read and write fluently. Through work programs such as teaching reading, writing, Quran recitation, memorization (tahfiz), and Islamic jurisprudence (fiqh), as well as introducing Indonesian culture through dance, song, traditional games, and handicrafts, this activity aims to revitalize knowledge while reinvigorating a sense of pride in Indonesian identity. The results of the activity demonstrate that the involvement of KKN students is able to meet the learning needs of immigrant children while strengthening national and cultural values ​​in the younger generation living abroad.